(untitled) (INNOVATIVE ECONOMY, 2020)
Yarova B.M. ECONOMIC AND LEGAL MODELS OF INSTITUTIONALIZATION OF THE RIGHTS OF THE STATE TO LAND RESOURCES Purpose. The aim of the article is detailed analysis of the powers of state authorities and local self-government and proposals for their redistribution and implementation of the principle of subsidiarity and the ability of local communities. Methodology of research. In the work as a methodological basis, scientific methods of cognition were used, based on a systematic approach to solving the problems posed. To achieve this goal, a number of general and special scientific methods of research were used: dialectical; monographic (when processing scientific publications); historical (in analyzing the European experience of land management in different periods); system analysis (in the study of the scope of powers of power structures on the disposal of lands); method of analogies and comparisons (in the study of world experience); complex analysis (in the formation of conclusions and proposals for solving the tasks); statistical (when processing statistical data), etc. Findings. The essence of the concept "institutionalization of the state’s rights to land resources" is substantiated. The existing distribution of powers between the authorities and local self-government has been explored and analyzed. The main provisions of the concept of the functioning of a specialized institution for the management of the National Academy of Sciences of Ukraine are disclosed. It is justified to introduce the principle of subsidiarity and the ability of local communities. Originality. Scientific approaches to the implementation of the new model of trust management of the lands of the National Academy of Sciences of Ukraine are scientifically grounded. A variant of delegation of powers between authorities and local self-government on land resources management is determined. Practical value. The findings can be used in the future to effectively and efficiently manage land resources, by transferring powers to local governments under the disposal of state-owned lands and introducing the principle of subsidiarity and the ability of local communities. Key words: land management; state property; powers; orders.